2022
DOI: 10.1177/09544062211064966
|View full text |Cite
|
Sign up to set email alerts
|

Integration modeling and control of a 12-degree-of-freedom macro–micro dual parallel manipulator

Abstract: Parallel manipulator systems with large workspace and high-accuracy positioning are attractive for a variety of accuracy engineering applications. In this article, a new 12-DOF macro–micro dual parallel manipulator is presented, which comprises a 6-PSU macro symmetrical parallel manipulator and a 6-SPS micro orthogonal parallel manipulator. This novel mechanism can not only realize a large range of movement but also accurate positioning. To achieve high-accuracy control, a macro–micro integrated model of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The sliding mode controller featuring vibration compensation was recently developed in DDFS to address the unpredictable synchronous inaccuracy. It implies nonlinear elements such as servo properties' variation and mechanical connection [91,102,107,108]. Le-Bao Li et al [109] integrated adaptive sliding mode control (ASMC) into a ring coupling synchronization control to harmonize the motion of multiple motors so that their speed tracking errors converging to zero requires stabilizing the speed tracking of a single motor.…”
Section: Modern Vibration Control Methodsmentioning
confidence: 99%
“…The sliding mode controller featuring vibration compensation was recently developed in DDFS to address the unpredictable synchronous inaccuracy. It implies nonlinear elements such as servo properties' variation and mechanical connection [91,102,107,108]. Le-Bao Li et al [109] integrated adaptive sliding mode control (ASMC) into a ring coupling synchronization control to harmonize the motion of multiple motors so that their speed tracking errors converging to zero requires stabilizing the speed tracking of a single motor.…”
Section: Modern Vibration Control Methodsmentioning
confidence: 99%
“…Ku, S. S. et al designed and fabricated a nanometer-precision 3-DOF positioner capable of combining a fast tool servo and motor-driven feedback controller with a tracking resolution of 2 nm [ 16 ]. A new 12-DOF macro/micro dual parallel manipulator was presented; the experimental results showed that the system had good performance, the translational precision could reach 15 μm, the rotation precision could reach 0.35′, and the precision of the micro-manipulator was more than ten nanometers [ 17 ]. with the macro/micro dual-drive platform designed by Dong, W. et al, the macro-drive used a sonic motor, and the micro-drive used PZT; the experiment result showed that the positioning accuracy of the system could reach 10 nm [ 18 ].…”
Section: Introductionmentioning
confidence: 99%